Measurement centration and zone diameter in anterior, posterior and total corneal astigmatism in keratoconus. Issue 8 (10th July 2017) - Fredriksson, Anneli; Behndig, Anders
Abstract: Purpose: To investigate the central and paracentral astigmatism and the significance of centration and measurement zone diameter compared to a 3‐mm pupil‐centred measurement zone in keratoconus and in healthy eyes. Methods: Twenty‐eight right eyes from 28 KC patients with an inferotemporal cone were selected according to specified criteria based on Oculus Pentacam HR ® measurements and were matched with healthy control eyes. The flat (K1) and steep (K2) keratometry readings were registered from the 'Total Corneal Refractive Power' (TCRP) display as well as the anterior and posterior corneal astigmatism displays (ACA and PCA, respectively). Astigmatic power vectors KP0 and KP45 were calculated and analysed for a 6‐mm and two 3‐mm zones centred on the corneal apex and the pupil, and for 8 paracentral 3‐mm zones. Results: The astigmatism was generally higher in KC. Many astigmatic values in KC differed between the 3‐mm pupil‐centred and the 3‐ and 6‐mm apex‐centred zones in KC. In the controls, no corresponding differences between measurement zones were seen, apart from PCA, which differed. The magnitude and direction of KP0 and KP45 varied greatly between the paracentral measurements in KC. Conclusion: Centration and measurement zone diameter have great impacts on the astigmatic values in KC. A small pupil‐centred measurement zone should be considered when evaluating the astigmatism in KC.